The effectiveness of miswak (Salvadora persica L. and Azadirachta indica A. Juss.) practices in reducing plaque and gingivitis among adults: A systematic review and meta-analysis - Haslinda Ramli; Khairun Nain Nor Aripin; Rohazila Mohamad Hanafiah; Shahida Mohd Said; Tuti Ningseh Mohd Dom (Elsevier, 2024)
Indexed by Scopus/ERA